Left atrial appendage closure in patients with a reduced left ventricular ejection fraction: results from the multicenter German LAARGE registry - Fastner, Christian; Brachmann, Johannes; Lewalter, Thorsten; Zeymer, Uwe; Sievert, Horst; Borggrefe, Martin; Weiß, Christian; Geist, Volker; Krapivsky, Alexander; Käunicke, Matthias; Mudra, Harald; Hochadel, Matthias; et al. (Clinical research in cardiology, 2020)
Interventional left atrial appendage closure (LAAC) effectively prevents thromboembolic events in atrial fibrillation patients. Impaired left ventricular ejection fraction (LVEF) increases not only the thromboembolic risk but also the complication rates of cardiac interventions. The LAAC procedure’s benefit in patients with an impaired LVEF, therefore, has yet to be investigated.
Gesehen am 09.12.2021